Correction: Venous congestion affects neuromuscular changes in pigs in terms of muscle electrical activity and muscle stiffness. - Keun-Tae Kim; Duguma T Gemechu; Eunyoung Seo; Taehoon Lee; Jong Woong Park; Inchan Youn; Jong Woo Kang; Song Joo Lee (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0289266.].